If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(y + -1) = 5y + 3 Reorder the terms: 6(-1 + y) = 5y + 3 (-1 * 6 + y * 6) = 5y + 3 (-6 + 6y) = 5y + 3 Reorder the terms: -6 + 6y = 3 + 5y Solving -6 + 6y = 3 + 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. -6 + 6y + -5y = 3 + 5y + -5y Combine like terms: 6y + -5y = 1y -6 + 1y = 3 + 5y + -5y Combine like terms: 5y + -5y = 0 -6 + 1y = 3 + 0 -6 + 1y = 3 Add '6' to each side of the equation. -6 + 6 + 1y = 3 + 6 Combine like terms: -6 + 6 = 0 0 + 1y = 3 + 6 1y = 3 + 6 Combine like terms: 3 + 6 = 9 1y = 9 Divide each side by '1'. y = 9 Simplifying y = 9
| -5z-5=-2z+10 | | 2(6)+3(-4)-(-2)=2 | | 15-11=2(x-8) | | 6(y-1)=5y+4 | | 20x+4=6x+4 | | -4(y+1)=0 | | 20x+4=8x+18 | | 4x^2-12x+9=equation | | 2/3x-5/3x | | 4(y+3)=2y+20 | | 3(6)-3(-4)+10(-2)=10 | | 30=5d-3d | | -2.24n=-12.168 | | x-12=x/10 | | 7x-1=8x+2 | | X-3-3x=3(1+x) | | y^4+12y^2+36=0 | | n/-15=5.3 | | 5(2x+6)=55 | | 1.6=4y+20.4 | | 2cos(x)-3x=0 | | 3x+4=9.5 | | n/14.3=-5 | | -0.166666666667= | | 0.5(y+8)=2(y-1) | | 7+8q=7q | | H=-16t^2+24t+40 | | -2x-1=2x+15 | | n/-12.168=-2 | | z+iz+1=0 | | 12(n+8)=132 | | 10(x+3)-9x-4=x-5+3 |